Reintroduction of gut microbiota improves liver regeneration in germ-free mice - Amin AR; Antony M Wheatley; Raman NF Aqilah; Fergus Shanahan; Mohd Hairulhisyam Ngatiman; Nur Fariha Mohd Manzor; Marlini Muhamad (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology